Copper based transparent solar heat rejecting film on glass through in-situ nanocrystal engineering of sputtered TiO2. Issue 2 (15th January 2022) - Nawade, Ashwini; Ramya, Kunchanapalli; Chakrabortty, Sabyasachi; Bamola, Priyanka; Sharma, Himani; Sharma, Mohit; Chakraborty, Krishnendu; Ramakrishna, Seeram; Biring, Sajal; Shun Wong, Terence Kin; Kumar, Avishek; Mukhopadhyay, Sabyasachi; et al.
Abstract: Sputter grown copper (Cu) and titanium dioxide (TiO2 ) based transparent solar heat rejecting film has been developed on glass substrates at room temperature for energy saving smart window applications. The performance of as-deposited ultra-thin TiO2 /Cu/TiO2 multilayers was elucidated, wherein the visible transmittance of the multilayer significantly depends on the crystal quality of TiO2 layers. In-situ nanocrystal engineering of TiO2 films with optimized sputtering power improves crystallinity of nano-TiO2 domains. The transparent heat regulation (THR) coating with an average transmittance of ∼70% over the visible spectral regime and infra-red reflectance of ∼60% at 1200 nm was developed at room temperature. Optical characterization, X-ray diffraction (XRD), high resolution-transmission electron microscopy (HR-TEM) and atomic force microscopy (AFM) have been utilized to analyze the crystallinity of TiO2 and quality of the multilayered structure. TiO2 /Cu/TiO2 based prototype device has been demonstrated for the energy saving smart windows application.